Rupture of Couvelaire uterus-a very rare case report - Singhal, Savita Rani; Suneja, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Couvelaire uterus is a complication seen in some severe forms of abruptio placentae. A careful watch and early identification can prevent grave maternal and fetal outcome. In literature, there are very few cases reported of rupture of Couvelaire uterus as it is a very rare entity. Our study highlights a case of 24 year old with nine months amenorrhea presented with abruption placenta and intrauterine fetal death. Diagnosis of ruptured Couvelaire uterus made and the same was repaired and managed. We were able to save the mother successfully.